Sosialisasi Kesehatan Reproduksi Sebagai Upaya Peningkatan Lifestyle Remaja Yang Sehat dan Unggul Di Desa Tuah Mesade - Halimatussakdiyah Lubis; Fika Lestari (Pusat Riset dan Inovasi Nasional, 2024)
Period most vulnerable to experiencing reproductive health problems such as early pregnancy, unsafe abortion which can cause the death of mother and child, depression, sexually transmitted infections (STIs) such as Human Immunodeficiency Virus (HIV), sexual harassment, infertility, and malignancies such as cervical cancer. Adolescents begin to focus on behavior that is associated with adult status, namely smoking, drinking alcohol, using drugs, and engaging in promiscuous sexual acts which are quite disturbing. Community Service